Comrade: The Zero-level of Communism - Dean, Jodi (Stasis, 2018)
Drawing from Andrei Platonov’s Chevengur, I present the figure of the comrade as the zero-level of communism. Platonov’s comrades persist in a postrevolutionary zone without workers, without classes, where the remainders of the old order have nothing but each other. Their condition of deprivation, where the persistence of each depends on the persistence of all, supplies the ground upon which to build communism. The comrade is the zero-level of communism because it designates the relation between those on the same side of the struggle to produce a new set of free, just, and equal social relations, relations without exploitation. Their relation is political, divisive. And it is intimate, intertwined with the sense of how desperately each depends upon the other if all are to persevere. I test this account of the comrade through the counter-intuitive case of the Communist Party of the United States. Although seemingly far removed from the Chevengurian communist project, the CPUSA nonetheless worked to establish the zero-level necessary for the communist movement: comradeship between black and white workers. At the basis of this comradeship was an understanding of racism as a condition of deprivation to be redressed through deprivation. Racism deprives the working class of solidarity. Solidarity requires that white workers deprive themselves of white privilege, the “wages of whiteness,” to use W.E.B. Dubois’s term. Hence, the Party focused, for a while, on establishing the zero-level of comradeship by devoting itself to the struggle for racial equality. If solidarity is possible, it is because the abolition of white supremacy leaves comrades to start anew.